The Story of Creation as Told By Theology and By Science - Ackland, T. S. (Thomas Suter), 1817-1892 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Story of Creation as Told By Theology and By Science" by T. S. Ackland is a scholarly examination exploring the intersection of biblical creation narratives and modern scientific understanding, likely written in the late 19th century. The text delves into the foundational aspects of creation as perceived through theology while addressing the challenges posed by scientific discoveries in fields such as geology, astronomy, and physiology. Ackland aims to reconcile the differences between the two perspectives, examining alleged contradictions and invoking deeper interpretations of the biblical text. The beginning of the work presents a framework where Ackland articulates the necessity of understanding the creation narrative as a critical part of divine revelation. He emphasizes that the theological account should not be seen as at odds with scientific findings but instead as a potential reflection on the limitations of both ancient understanding and contemporary interpretations. By discussing specific examples such as ancient geological formations and astronomical phenomena, Ackland positions the biblical account within a broader context of knowledge, suggesting that a thoughtful approach to both scripture and science may yield a harmonious understanding. He does not shy away from identifying the complexities and potential inaccuracies in traditional readings, aiming instead for a more nuanced appreciation of creation as a process that might include many ages of development. (This is an automatically generated summary.)
The case stated -- Difficulties in geology -- Difficulties in astronomy -- Difficulties in physiology -- Science a help to interpretation.
Release date is 2003-10-01
Robert Rowe, Charles Franks and the Online Distributed Proofreading Team
Keywords: Religion and science; Creation; Bible and science